Chondroitin Sulfate‐E Binds to Both Osteoactivin and Integrin αVβ3 and Inhibits Osteoclast Differentiation. Issue 10 (October 2015) - Miyazaki, Tatsuya; Miyauchi, Satoshi; Anada, Takahisa; Tawada, Akira; Suzuki, Osamu
ABSTRACT Integrins and their ligands have been suggested to be associated with osteoclast‐mediated bone resorption. The present study was designed to investigate whether chondroitin sulfate E (CS‐E), which is one of the sulfated glycosaminoglycans (GAGs), is involved in osteoactivin (OA) activity, and osteoclast differentiation. The binding affinity of sulfated GAGs to integrin and its ligand was measured using biotin‐labeled CS‐E, and the osteoclast differentiation was evaluated by tartrate‐resistant acid phosphatase staining and a pit formation assay. CS‐E as well as CS‐B, synthetic chondroitin polysulfate, and heparin inhibited osteoclast differentiation of bone marrow‐derived macrophages. Pre‐coating of OA to synthetic calcium phosphate‐coated plates enhanced the osteoclastic differentiation of RAW264 cells, and addition of a neutralizing antibody to OA inhibited its differentiation. CS‐E bound not only to OA, fibronectin, and vitronectin, but also to its receptor integrin αVβ3, and inhibited the direct binding of OA to integrin αVβ3. Furthermore, CS‐E blocked the binding of OA to cells and inhibited OA‐induced osteoclastic differentiation. On the other hand, heparinase treatment of RAW264 cells inhibited osteoclastic differentiation. Since binding of OA to the cells was inhibited by the presence of heparan sulfate or heparinase treatment of cells, heparan sulfate proteoglycan (HSPG) was also considered to be an OA receptor. Taken together, the present results suggest that CS‐E is capable of inhibiting OA‐induced osteoclast differentiation by blocking the interaction of OA to integrin αVβ3 and HSPG. J. Cell. Biochem. 116: 2247–2257, 2015. © 2015 Wiley Periodicals, Inc.